2016
DOI: 10.1093/sysbio/syw016
|View full text |Cite|
|
Sign up to set email alerts
|

Integrative Taxonomy Recognizes Evolutionary Units Despite Widespread Mitonuclear Discordance: Evidence from a Rotifer Cryptic Species Complex

Abstract: Mitonuclear discordance across taxa is increasingly recognized as posing a major challenge to species delimitation based on DNA sequence data. Integrative taxonomy has been proposed as a promising framework to help address this problem. However, we still lack compelling empirical evidence scrutinizing the efficacy of integrative taxonomy in relation to, for instance, complex introgression scenarios involving many species. Here, we report remarkably widespread mitonuclear discordance between about 15 mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
162
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 112 publications
(176 citation statements)
references
References 115 publications
14
162
0
Order By: Relevance
“…The absence of hybrids in the B. plicatilis complex is in stark contrast with what is known in the B. calyciflorus complex, for which a high level of hybridization and mitonuclear discordance between cryptic species is present (Papakostas et al, 2016). The reasons for such differences in the level of hybridization in the two species complexes of the same genus are still unknown and deserve further investigation.…”
Section: Support For Species Identitymentioning
confidence: 71%
“…The absence of hybrids in the B. plicatilis complex is in stark contrast with what is known in the B. calyciflorus complex, for which a high level of hybridization and mitonuclear discordance between cryptic species is present (Papakostas et al, 2016). The reasons for such differences in the level of hybridization in the two species complexes of the same genus are still unknown and deserve further investigation.…”
Section: Support For Species Identitymentioning
confidence: 71%
“…The B. plicatilis complex is a strong candidate taxon because it is by far the most well-documented and resolved monogonont species complex. While B. calyciflorus has also been the subject of many studies, its species complex is yet poorly understood although efforts are currently being done to fill this knowledge gap (Papakostas et al, 2016). A major advantage of B. calyciflorus is that it is a common freshwater species in many parts of the world.…”
Section: Monogononts: Underappreciated Opportunitiesmentioning
confidence: 99%
“…Since the discovery of cryptic species in Brachionus plicatilis (Gómez & Serra, 1995;Gómez et al, 2002), the number of rotifer taxa known to be composed of cryptic species has steadily increased during the last decade (Walsh et al, 2009;Obertegger et al, 2012). Furthermore, several studies have provided evidence for substantial ecological segregation among such species (Gabaldón et al, 2015a;Papakostas et al, 2016). Because cryptic species are often found to be sympatric Gabaldón et al 2015b, Papakostas et al, 2016, the potential occurrence of multiple species in experimental populations of microevolution studies may incur considerable risks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, the DNA sequences of the resting eggs of B. calyciflorus from the pre-, during and post-pollution phases represented the same mtDNA haplotype through time. This species is highly variable in the analysed mtDNA fragment (Papakostas et al, 2016); thus, the fact that only one haplotype was found in the lake suggests that this species was able to quickly adapt locally through priority effects and monopolisation (De Meester et al, 2002), and no foreign mtDNA haplotypes managed to colonise the lake during its fluctuating conditions. …”
Section: Review Of Rotifers From Lake Ortamentioning
confidence: 99%